2016
DOI: 10.1158/1541-7786.mcr-15-0229-t
|View full text |Cite
|
Sign up to set email alerts
|

The CBM Complex Underwrites NF-κB Activation to Promote HER2-Associated Tumor Malignancy

Abstract: The HER2/Neu protein is overexpressed in a large fraction of human breast cancers. NF-kB is one of several transcription factors that are aberrantly activated in HER2-positive breast cancers; however, the molecular mechanism by which HER2 activates NF-kB remains unclear. The CARMA3-BCL10-MALT1 (CBM) complex is required for GPCR-and EGFR-induced NF-kB activation. In the current study, the role of the CBM complex in HER2-mediated NF-kB activation and HER2-positive breast cancer was investigated. Interestingly, H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
(36 reference statements)
3
28
0
Order By: Relevance
“…6E). Consistent with our observations in the K14 knockdown dataset, we observed that nine of these genes were previously reported in metastasis regulation, including in metastatic niche, vascular remodeling, and immunosurveillance, including Tnc, AdamTs1, Jag1, as well as Card10, Cav1, Ereg, Lgr5, Slpi, and Ptgs2 (29,(35)(36)(37)(38). Core genes showed evidence of multiple physical and genetic interactions and occurrence along common pathways (Fig.…”
Section: K14 Expression Is Required For Distant Metastasis and Regulasupporting
confidence: 90%
“…6E). Consistent with our observations in the K14 knockdown dataset, we observed that nine of these genes were previously reported in metastasis regulation, including in metastatic niche, vascular remodeling, and immunosurveillance, including Tnc, AdamTs1, Jag1, as well as Card10, Cav1, Ereg, Lgr5, Slpi, and Ptgs2 (29,(35)(36)(37)(38). Core genes showed evidence of multiple physical and genetic interactions and occurrence along common pathways (Fig.…”
Section: K14 Expression Is Required For Distant Metastasis and Regulasupporting
confidence: 90%
“…Finally, an increasing number of publications support a role for aberrant MALT1 signaling in the development of non-lymphoid cancers, such as glioblastoma (127), breast cancer (18, 128, 129), melanoma (130), lung cancer (18), and various other carcinomas (1, 131, 132). In these cancers, MALT1 seems to be activated by constitutive signaling from GPCRs or the EGFR via CARMA3 and/or by overexpression of MALT1 through various mechanisms.…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 99%
“…For breast cancer, two different subtypes, which are HER2 or angiotensin II receptor (AGTR1) positive, have been described to be addicted to CBM signaling via CARMA3 (18, 128, 129). Interestingly, these two subsets show abnormal expressions of AGTR1 or HER2 in a mutually exclusive manner (128).…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…CARD11 (CARMA1), expressed in lymphoid cells, is activated upon B-and T-cell receptor engagement, and gain-of-function (GoF) mutations in the genes encoding CARD11, Bcl10, and Malt1 have been associated with a number of lymphoid malignancies (Gaide, et al, 2002;Juilland and Thome, 2016;Pomerantz et al, 2002;Wang et al, 2002). Similarly, CARD10 (CARMA3), expressed in epithelial tissue and activated by G protein-coupled receptor stimulation, has been linked to the progression of various carcinomas Pan et al, 2016;Xia et al, 2016;Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%